PENGARUH PERMAINAN DAN KEMAMPUAN MENYIMAK TERHADAP KEMAMPUAN BERCERITA - RACHMI, TITI (Jurnal Pendidikan Usia Dini, 2015)
Abstract: The aim of the research is to analyze the influence between play and listening ability to the story telling skills of kindergarten student in Tangerang. This research spent two month since early march until april using experimental factorial 2x2 method with treatment by level. Sample of this research is selected 33 children in kindergarten RA Al Muhajirin and 30 children in kindergarten TK Bina Madani with a total of 63 children were determined by multistage sampling technique. Based on the analysis of data, thus it can be concluded that (1) story telling skills student that is given dramatic play is higher than story telling skills that is given constructive play, (2) there is interaction between play with listening skills trough story telling skills of kindergarten students, (3) story telling skill students that have higher listening skills and given dramatic play is higher than a group of student that is given constructive play, (4) story telling skills student that have lower listening skills and given dramatic play is lower than a group of student that is given constructive play. Keyword: Story Telling Skills, Dramatic and Constructive Play, Listening Ability.